Competing for the Audience's Time: Comparing Science News with Health News and Political News. Issue 4 (2nd October 2019) - Sarrina Li, Shu-Chu
Abstract : Science and health news are closely related to the public's science literacy, and political news is very popular in Taiwan. The existing literature does not include studies that examine how science, health, and political news satisfy individuals' various gratifications. This study adopted niche theory to compare science, health, and political news regarding each news type's capabilities to fulfill individuals' needs for four different types of gratifications. The study used two methods: the first involved conducting 23 intensive interviews, and the second utilized a nationwide telephone survey, from which this study obtained 949 valid questionnaires.